Sharing global regulatory space: transatlantic coordination of the G20 OTC derivatives reforms (2020)
The governance of the global market for over-the-counter (OTC) derivatives has undergone a metamorphosis. Set in motion by the Group of Twenty (G20) 2009 summit in Pittsburgh, the regulatory overhaul has transformed what used to be a relatively harmonious and transnational legal regime into a global regulatory space which – like all regulatory spaces (Hancher and Moran 1998) – is highly contested. In the light of the hypotheses developed in Chapter 1 of this book, this chapter evaluates the implementation and coordination of the globally agreed derivatives reforms in and between the United States and the European Union (for earlier research on this topic, see Godwin et al. 2017). The chapter focuses specifically on the possible implications of coordination challenges for regulatory structures. The hypothesis is that, together with the risk of regulatory arbitrage, regulatory competition contributes to regulatory centralisation in internal regulatory structures.